(untitled) (AYUSHDHARA, 2024)
Health is undeniably an essential factor that plays an important role in every woman’s wellbeing. Cervical, uterine, and vaginal prolapse is known as utero-vaginal prolapse. 2-20% is the global prevalence of uterine prolapse, according to WHO estimates for women under 45 given that the range of this scenario is similar to that of India about 15-20%. Uterine prolapse does not pose a life threatening hazard but it can cause bowel or bladder incontinence which can impair quality of life, sexual dysfunction and negative body image. Prasramsini and Phalini Yonivyapada are among 20 Yoni Vyapadas mentioned in Ayurveda classics explained in Sushruta Samhita Uttartantra 38th chapter Yonivyapada Pratisedha Adhyaya. Ayurvedic classics like Vedic scripts, Upanishad, Charak samhita, Ashtanga Sangraha and Astanga Hridaya have not mentioned Prasramsini as a separate disease. They have used term Sransta, Prasrata, Dusthita yoni, Nisrita Yoni, Sthanapvrit Yoni. In Ayurvedic classics there are variety of conservative treatments like Shodhan Chikitsa, Shaman Chikitsa, Sthanik Chikitsa have mentioned.